(untitled) (Biological Sciences - PJSIR, 2025)
The highly integrated data obtained from diverse omics fields has enabled us to study complex relationships among organisms and to identify novel genotypic and phenotypic targets of lethal diseases. In the age of precision medicine, data obtained from various omics modalities such as transcriptome, epigenome and metabolome prove to be very useful in health and medicine. The data combined from different omics levels also proved to be very fruitful in the study of different types of cancer at the single cell level. In addition to cancer, a single cell study provides deep insight into the underlying mechanisms of various infectious diseases. Besides this, single cell technology is also helpful in discovering new cells and in tracing ancestral lineages of different species. Moreover, the role of our immune cells in response to these infective agents and new drug targets can also be studied using these omics technologies. These different omics levels provide authentic combined data and hence they are helpful in stem cell research. Circulating tumor cells, prenatal diagnosis of fatal diseases and lung malfunctioning can only be studied at single cell resolution. This review article aims to comprehend the applications of omics technology in the study of lethal diseases which would only be possible at the single cell level and to find potent drug targets.